ASSESSING THE SUITABILITY OF THE LEE-CARTER MODEL IN MODELLING MORTALITY DATA WITH VARYING bx PARAMETER - Shelleng, A. U.; Dikko, H. G.; Garba, J.; Alhaji, B. B. (FUDMA JOURNAL OF SCIENCES, 2023)
The Lee-Carter model, developed by Lee and Carter in 1992 is one of the most influential model among others that is used for mortality projection. Although the model's performance has so far been examined in a variety of situations, its effectiveness in modeling mortality data with varying speeds of change in mortality across ages and the ability to detect trends in mortality index more precisely over time has not been studied. The method traditionally used in the Lee-Carter model shows obvious drawbacks in describing the shape of future mortality. The effectiveness of the Lee-Carter model to model mortality data with varying speeds of change in mortality was investigated. The model was applied to mortality data with both constant and varying speeds of change for female sub population. Results show that the Lee-Carter model is not good for mortality data with varying speeds of change.
Keywords: Lee-Carter model; ARIMA; Singular value Decomposition; Mortality Rate